Pattern of Lipid Profile and Blood Pressure in Patients with Nonalcoholic Fatty Liver Disease (NAFLD) - Chowdhury, Md Fazlul Karim; Zaman, Khandkar Mahabub Uz; Hasan, Md Abual; Amin, Md Al; Saha, Krishna Pada; Ashrafuzzaman, Md; Islam, Nazia; Ghosh, Chanchal Kumar (Journal of Shaheed Suhrawardy Medical College, 2022)
Background: Non-alcoholic fatty liver disease (NAFLD) is associated with metabolic syndrome (MS) such as hypertension, type 2 diabetes mellitus, dyslipidaemia and obesity. NAFLD is considered as hepatic manifestation of metabolic syndrome (MS). Objectives: The aim of this study was to see the pattern of lipid profile and blood pressure in NAFLD patients. Materials and methods: This cross sectional study was carried out in the department of gastroenterology, BSMMU, Dhaka, Bangladesh from October 2016 to March 2017. A total of 100 patients included in this study underwent abdominal ultrasonography after excluding known case of liver disease with other etiology. Results: The study population were categorized as NAFLD and normal group on the basis of abdominal ultrasonography. NAFLD and normal subjects were 55% and 45% respectively. The mean age was 41.34 + 10.88 years. Male were 62% and 38% were female.40% of study subjects were overweight, 23% were obese and 37% had normal bodyweight. Body mass index (BMI) was higher in NAFLD group; 25.10 ± 1.75 vs 21.64 ± 2.62 , P < 0.001). Dyslipidemia was present in 47% of study population. Total cholesterol (TC) (195.5±45.98 vs 140.33±47.86 mg/dl, P < 0.001), Low density lipoprotein-cholesterol (LDL-C) (120.28±43.95 vs 95.15±44.90 mg/dl, P < 0.001) and Triglyceride (TG) (230.50 ± 48.96 vs 148.40±46.43 mg/dl , P < 0.001) was higher and High density Lipoprotein (HDL) (32.69±5.49 vs 39.91±5.74 mg/dl, P < 0.001) was lower in NAFLD group in comparison to normal group. Systolic and diastolic blood pressure (BP) was also significantly higher in NAFLD group (135±12 vs 121±9 mm Hg , P < 0.001) and 82±4 vs 74±3 mm Hg (P < 0.001) respectively. Conclusion: Higher prevalence of dyslipidemia was found in NAFLD patients. TC, LDL-C , TG and blood pressure was significantly higher in NAFLD patient in comparison to normal group. J Shaheed Suhrawardy Med Coll 2021; 13(1): 68-74